(untitled) (Journal of Applied Learning and Teaching, 2020)
Professor James Tooley (born in 1959 in Southampton, England) is the Vice Chancellor of the University of Buckingham since 1 October, 2020. Prior to that appointment, he was professor of educational entrepreneurship and policy at the University of Buckingham, with previous academic appointments at the Universities of Oxford, Manchester and Newcastle. His ground-breaking research on low-cost private education in developing countries has won numerous awards, including a gold prize in the first International Finance Corporation/ Financial Times Private Sector Development Competition, the Templeton Prize for Free Market Solutions to Poverty, and the IEA’s National Free Enterprise Award. His book based on this research, The beautiful tree (Penguin and Cato Institute), was a best-seller in India and won the Sir Antony Fisher Memorial Prize. He has also authored many other books. Building on his research, Prof Tooley has pioneered models of innovation in low-cost private education. He has co-founded chains of low-cost schools in Ghana, India, Honduras and, most recently, in England. In this extensive interview, we focus on James Tooley’s fascinating research on private education for the poor, but also, touch on a wide range of other topics, such as his unjust imprisonment in India, his own private school ventures in four continents, and the question of whether higher education is largely signaling or it truly builds human capital.